Closing the Gap: A Clinical Instructor and Preceptor Academy to Address Educator Shortages and Improve Teaching Confidence - Elizabeth L. Woods; Jeannie B. Weston; Maggie S. Pustinger; Desiree M. Clement; Rose K. Hayes; Quyen T. Phan (The Journal of Continuing Education in Nursing, 2026)
Background: Clinical instructors and preceptors (CIPs) are essential to nursing education, yet many registered nurses and advanced practice registered nurses are asked to assume CIP roles and expected to initiate those roles without formal training, potentially compromising the confidence of CIPs and the quality of instruction. Method: The authors designed and implemented a comprehensive academy to address CIP learning needs in underserved Southeastern U.S. communities. The development process began with a needs assessment conducted across the region to inform curricular design. Formative and summative evaluation data were collected at each program cycle, enabling continuous program refinement. Results: The academy offers an accessible, affordable training option for CIPs, demonstrating how structured professional development can strengthen the nursing workforce in resource-limited settings. The ongoing collection and analysis of evaluation data enabled iterative improvements to curriculum content, delivery methods, and program structure. Conclusion: The academy shows how structured, evidence-based professional development can strengthen the nursing workforce in resource-limited settings, offering a replicable and sustainable model.